Querido diário... o que revelam as narrativas sobre ludicidade, formação e futura prática do professor que ensina(rá) matemática nos anos iniciais - Silva, Américo Junior Nunes da (2018)
This study aims to investigate what narratives of undergraduates of the Pedagogy course of UFSCar, constructed during the formation, about the playfulness, the teaching of mathematics and the being a teacher who teaches mathematics in the initial years. For this, therefore, we are based on the presuppositions of a narrative research, choosing it as the best way to understand the experience and embracing the narratives, simultaneously, as a method and as a phenomenon to be studied. The field texts, constructed throughout the research, were the diaries and narrative interviews conducted. We hope to understand, and this is the thesis that we defend, as the construction of these diaries and the anamnesis of their lives may have been formative and have influenced the constitution of the teaching identity of the participants. The look we have given focuses on the narratives produced during the last two years, from initial contact with the subject of "Mathematics: contents and their teaching", in the second half of 2015, to the narrative interview conducted in the first half of 2017. For composition of the research texts we consider the experiences lived and what the five students revealed in their field texts. We try to present them as a journal entry and taking into account the dynamic movement of experiences. These narratives were analyzed, therefore, in view of the following narrative movement: i) Look at what proposes the course of Pedagogy of UFSCar in search of evidence of how this formation occurs and how it was signified by the students; ii) Focus on the initial narratives and glimpses of the participants' life histories, in search of the revealed conceptions about playfulness, and to become a teacher who will teach mathematics in the initial years; and iii) Narrate, therefore, our experiences with the discipline, in the movement of the own experience, to understand how they were meant, in order to broaden the look on the research puzzle. It was from the look to the Pedagogical Project that we perceive that there is an overvaluation of a specific profile of formation. From the history of the course and its connection, since its inception, with the issues of guidance and school administration and what the students presented to us, we noticed that prioritizing one aspect of training to the detriment of others. A greater concern or closer look at the teacher training that will teach mathematics in the early years and its playfulness, for example, have been silenced in the paper. Throughout the field texts we realize that the initial formation has a socializing influence and that it depends on the nature, the structure and the training model, as well as the beliefs and what the students bring and that were constructed throughout their histories of life. The students came to the research space with their stories and built beliefs about being a student and teacher, about mathematics and how to teach it. The process of writing about encounters and taking back, from the life story itself, how this construction of the relationship with mathematics took place, made it possible to demystify the fear and some difficulties that they had. We realized that the narratives produced during the training revealed a great deal about formation, playfulness, and being a teacher who taught mathematics in the early years. The life history elements of students in Pedagogy, recorded in journals during initial formation, focusing on mathematics and playfulness, reveal marks - positive and negative of mathematics -, provoke reflections and questions about being a teacher who will teach mathematics in the early years and give clues about the professional constitution of teachers.